PENGARUH KOORDINASI TERHADAP KINERJA PEGAWAI PEMUNGUT PBB PADA KECAMATAN PATARUMAN KOTA BANJAR - Benyamin Harits (Kebijakan : Jurnal Ilmu Administrasi, 2020)
This research based on main problem, that is the low of Employee Performance. These conditions predicted because of has not implemented yet of Coordination elements at PBB collector (Land and Building Tax) in Pataruman District, Banjar City. Approach in this research about Coordination and Employee Performance from Public Policy and Public Administration as master theory to develop science area of public administration. Research method is explanatory survey descriptive. This method used to explain social phenomenon which in this case used to check influence of Coordination (X) as independent variable to employee performance (Y) as dependent variable. This research use quantitative analysis usage Path Analysis Method meant to know value of influence Coordination variable to Employee Performance at PBB collector (Land and Building Tax) in Pataruman District, Banjar City either through simultan and also by parsial. Result of research indicate that by simultan, influence of Coordination (X) to Employee Performance (Y) equal to 60,48%. As for influence of other variable to Employee Performance (Y) equal to 39,52%. While by partial, influence of Coordination (X) which consist of six Coordination elements covering: element of Units (X1) have a non significance effect to Employee Performance (Y) equal to -0,31%, element of Sources (Potency) (X2) have a non significance effect to Employee Performance (Y) equal to 16,31%, element of Cohesion (X3) have a significance effect to Employee Performance (Y) equal to 23,24%, element of Motion Activity (X4) have a non significance effect to Employee Performance (Y) equal to -5,51%, element of Harmony (X5) have a significance effect to Employee Performance (Y) equal to 13,62% and element of Same Direction (Target) (X6) have a significance effect to Employee Performance (Y) equal to 13,11%. From six Coordination elements that giving dominant influence by parsial to Employee Performance is element of Cohesion (X3) that have a significance effect to Employee Performance (Y) equal to 23,24%. Researcher can conclude that Coordination influentialy in positive and significance to Employee Performance at PBB collector (Land and Building Tax) in Pataruman District, Banjar City. That accross the board Coordination has been executed and implemented according to Employee Performance factors